Discourse Connectors Pada Peringkasan Dokumen Berbahasa Indonesia - Irwan Darmawan; Nirwana Haidar Hari (Universitas PGRI Kanjuruhan Malang, 2021)
Documents that have a lot of content will make it difficult for readers to find the essence or topics in a document. Therefore, a system that can summarize documents is needed to find the topics discussed by the document. In the research, the documents used as test materials were the final project papers of informatics engineering students, Madura University. Various methods have been applied in summarizing a document, including using the cosine of similarity to determine the weight and the relationship between one sentence and another and then dumping the sentences which have small weight based on the threshold value of the user. If the length of a sentence has little weight, it does not mean that the sentence is not important when it comes to other sentences. Therefore a discourse connector is needed to connect one sentence to another sentence and then it is given weight according to the discourse connector formula. In this study, it is expected that the document has a better value than before as evidenced by a size that is higher than 70%